Lock the tropical forests up? no way - Sayer, Jeffrey A. (2001)
The author explores the pros and cons on whether tropical forests as national parks should be locked up and reserved or they should be managed directly and sustainably by local people for various benefits. An example is at Metut, a village adjacent to Bulungan Research forest in Indonesia where scientists from the Centre for International Research Centre (CIFOR) are studying effects of development of forest areas. In this remote place, the way of life is changing. Now outboard motors bring villagers relatively easy to the outside world while it took weeks by canoe a generation ago. Many of the younger men leave their village to seek employment in logging concessions. Even so, their lives still depend on the forests. The forest faces many threats, ranging from open-cast coal mining to illegal logging and the clearance of forest for oil palm plantations. These threats have also provided opportunities, as development has brought employment, roads and schools. Forests will only survive in Asia if they yield more benefits to the people who live in and around them. Industrial forestry and natur protection will be part of the solution. Both can create employment and generate revenues for local communities.